2018
DOI: 10.1113/ep086564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fetal hypothyroidism on uterine smooth muscle contraction and structure of offspring rats

Abstract: Thyroid hormones play an essential role in fetal growth. Hypothyroidism impairs reproductive function in both humans and animals. The aim of this study was to assess the effects of fetal hypothyroidism on uterine smooth muscle contraction and structure in the adult offspring. The control group of female Wistar rats consumed tap water, whereas the hypothyroid group received water containing 0.025% of 6-propyl-2-thiouracial throughout gestation from mating until delivery. Isometric contractility and histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
6
0
2
Order By: Relevance
“…The fetal thyroid milieu may play a role in initiating and maintaining uterine contractions during delivery in response to endogenous oxytocin. Fetal hypothyroidism had been found to reduce uterine contractions (amplitude and frequency) in response to oxytocin administration in rat mothers 24 . Another animal study linking oxytocin administration during delivery and maternal thyroid function reported that administration of intravenous oxytocin to rats decreased their TSH, FT4, and FT3 levels 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The fetal thyroid milieu may play a role in initiating and maintaining uterine contractions during delivery in response to endogenous oxytocin. Fetal hypothyroidism had been found to reduce uterine contractions (amplitude and frequency) in response to oxytocin administration in rat mothers 24 . Another animal study linking oxytocin administration during delivery and maternal thyroid function reported that administration of intravenous oxytocin to rats decreased their TSH, FT4, and FT3 levels 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model, hypothyroidism increased the threshold pressure of the bladder 17 . It has been demonstrated that the amplitude and frequency of uterine smooth muscle contractions in hypothyroid rats were significantly lower than in the control group 20 . Moreover, hypothyroidism has been related to the decreased function of the parasympathetic system as shown by analyzing R‐R intervals from electrocardiograms 21 .…”
Section: Discussionmentioning
confidence: 99%
“…17 It has been demonstrated that the amplitude and frequency of uterine smooth muscle contractions in hypothyroid rats were significantly lower than in the control group. 20 Moreover, hypothyroidism has been related to the decreased function of the parasympathetic system as shown by analyzing R-R intervals from electrocardiograms. 21 As a result, it seems that hypothyroidism can alleviate storage symptoms through an anticholinergic-like effect.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, thyroid hormones triiodothyronine (T3) and thyroxine (T4) are critical for normal development, growth and metabolic homeostasis [ 27 ]. Besides, thyroid hormone deficiency during pregnancy was reported in rat, which caused a decrease of litter size [ 28 ]. GnRH signaling pathway, and Ovarian steroidogenesis are classical signaling pathways related to follicle development.…”
Section: Discussionmentioning
confidence: 99%